Arctic flights of the Aries , 1951 - Mitchell, J. L. (Polar Record, 1952)
The Royal Air Force Flying College at Manby in Lincolnshire, England, was established in 1949. During a training course lasting one year, experienced pilots and navigators study all aspects of the operation of an aircraft as a weapon of war. Such an all-embracing syllabus calls for a knowledge of air operations, backed by practical experience, in all parts of the world. Those taking part are introduced to some of the problems peculiar to cold-weather operation in high latitudes by a number of summer air exercises in the arctic regions, and by liaison flights in the winter months to Alaska and Canada.